PENERAPAN ALGORITMA SURF PENDETEKSI OBJEK PADA AUGMENTED REALITY BERBASIS ANDROID - Ari Amir Alkodri Ari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
For the application of effective and efficient concepts in learning using interactive augmented reality technology. Multimedia learning is a form of interactive learning. Learning can be done in class or in the form of assignments at home. The impact of interactive learning greatly affects the quality of understanding for users. Based on testing from augmented reality technology, research, analysis and analysis of interactive interface design, processes and principles are carried out through human and computer interaction as well as user experience. The interface design method uses the Object Oriented Programming method and the Speeded Up Robust Features algorithm. The results showed that interactive augmented reality can provide new methods in the learning process and update learning content in the classroom. In short, this method increases student participation and enthusiasm, and increases learning effectiveness.